The genus Cnemidophorus (Squamata: Teiidae) in State of Piauí, northeastern Brazil, with description of a new species - Da Silva, Marcélia Basto; Ávila-Pires, Teresa C.s. (Zootaxa, 2013)
The state of Piauí, northeastern Brazil, is covered mainly by ‘cerrado’ (33% of the total area of the state) and ‘caatinga’ (37%) vegetations, with another 19% occupied by ecotonal zones. Piauí lies within the known distribution of the Cnemi-dophorus ocellifer species group, currently composed of ten species. Until recently only C. ocellifer (Spix, 1825), a name recognized to cover several species, was recorded from Piauí. Currently two other species are registered from Piauí: C. confusionibus Arias, Carvalho, Rodrigues and Zaher 2011 and C. venetacaudus Arias, Carvalho, Rodrigues and Zaher 2011. We analyzed the external and hemipenial morphology of specimens from different localities in the state and our re-sults indicate the presence of at least four species: C.cf. ocellifer, C. confusionibus, C. venetacaudus and C. pyrrhogularis sp. nov. Hemipenial analysis corroborates the existence of two subgroups within C. ocellifer species group. Cnemidopho-rus pyrrhogularis sp. nov., a member of the ocellifer subgroup, occurs in the northern part of Piauí, in ecotonal areas, and differs from the remaining species of the genus mainly on hemipenial morphology, number of femoral pores, number the lamellae under fourth finger and fourth toe, and color pattern. Diagnoses and hemipenis description of the four taxa are presented, as well as a detailed description of the new species.